Interrelation of speed-strength abilities and indicators of maximum aerobic power - Volkov, V. V.; Tambovtseva, R. V.; Miroshnikov, A. B. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to evaluate the relationship between the maximum aerobic power demonstrated in tests with different duration of the load and the maximum anaerobic power.